Treatment of textile wastewater using activated sludge process and hydrogen peroxide - Megat Mohd Noor, Megat Johari; Saed, Katayon; Abdullah, Abdul Ghani Liew (Federation of Engineering Institutions of Islamic Countries, 2006)
Increasing application of advance oxidation processes (AOPs) to industrial wastewater has been observed recently. However, an integrated approach of biological and chemical treatment of industrial wastewater also merits consideration. In this paper, the use of advance oxidation process using hydrogen peroxide on textile wastewater was studied for removal of chemical oxygen demand (COD), total organic carbon (TOC), colour and total suspended solids. The textile wastewater was treated using an activated sludge process (extended aeration) prior to oxidizing by hydrogen peroxide. Up to 99% of biodegradable compound was removed by the biological process whereas the non-biodegradable content being the larger component due to the nature of textile wastewater needed hydrogen peroxide concentration of is at 2ml/L (v/v) at a contact time of 30 minutes for optimum COD, TOC and colour removal.